2002
DOI: 10.1007/s00425-002-0739-z
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of phosphoinositide turnover in tracheary element differentiation in Zinnia elegans L. cells

Abstract: Mesophyll cells of Zinnia elegans L., cultured in the presence of phytohormones, will transdifferentiate and undergo programmed cell death to become tracheary elements, thick-walled cells of the xylem. This system is a model system for study of plant cell development and differentiation. We report that a high concentration of extracellular Ca(2+) is necessary during the first 6 h of culturing for tracheary elements to form. Extracellular Ca(2+) is still required at later times, but at a much lower concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…3A), the first peak of the response is likely due to an influx of extracellular Ca 2+ , whereas the second peak is due to a release of Ca 2+ into the cytoplasm from intracellular stores through IP 3 -dependent signaling pathway. Phospholipase C is also activated by Ca 2+ in plants as well as in animals (Miyakawa et al 2001, Zhang et al 2002. The Ca 2+ influx during the first peak of the response may participate in the activation of phospholipase C. Interestingly, oligosaccharide elicitors such as β-glucan, chitoheptaose and oligogalacturonides induce similar [Ca 2+ ] cyt transient peaks (Mithöfer et al 1999, Lecourieux et al 2002, suggesting that signals from different kinds of elicitors are mediated by similar Ca 2+ signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3A), the first peak of the response is likely due to an influx of extracellular Ca 2+ , whereas the second peak is due to a release of Ca 2+ into the cytoplasm from intracellular stores through IP 3 -dependent signaling pathway. Phospholipase C is also activated by Ca 2+ in plants as well as in animals (Miyakawa et al 2001, Zhang et al 2002. The Ca 2+ influx during the first peak of the response may participate in the activation of phospholipase C. Interestingly, oligosaccharide elicitors such as β-glucan, chitoheptaose and oligogalacturonides induce similar [Ca 2+ ] cyt transient peaks (Mithöfer et al 1999, Lecourieux et al 2002, suggesting that signals from different kinds of elicitors are mediated by similar Ca 2+ signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…3A), suggesting that increases in [Ca 2+ ] cyt are due to the influx of extracellular Ca 2+ . Phospholipase C, an enzyme producing IP 3 , is inhibited by neomycin and U-73122 (Zhang et al 2002). Neither of these inhibitors affected the first peak of the [Ca 2+ ] cyt transients, while both inhibited the second peak (Fig.…”
Section: Origins Of Ca 2+ For the Two Distinct Ca 2+ Transientsmentioning
confidence: 99%
“…1A). To look at the role of PI-PLC, we examined the effect of the PI-PLC inhibitor U73122 on DNA synthesis, because it is known that U73122 inhibits PI-PLC activity of different types of plant cells, both in vivo and in vitro (Coursol et al, 2000;Zhang et al, 2002). U73122 was added to the cells at concentration of 100 M, as in other studies with plant cells (Perera et al, 2001;Takahashi et al, 2001).…”
Section: Pi-plc Inhibitor Affects the Rate Of Dna Synthesismentioning
confidence: 99%
“…PLC activity was measured on microsomal membrane preparations, according to the method described by Zhang et al (2002) with a few modifications. Membrane protein (10 g) was incubated with 5 L of substrate micelles in a 50-L final volume of PLC assay buffer for 30 min at 37°C.…”
Section: Plc Assaymentioning
confidence: 99%
“…Since a free Ca 2+ pulse in the cytosol is one of the most important events in plant defense responses (Trewavas and Mahlo 1998), linking the Ins(1,4,5)P 3 signaling pathway with Ca 2+ signaling extends the influence of Ins(1,4,5)P 3 signal transduction to other cellular processes of plants. In fact, Ins(1,4,5)P 3 -Ca 2+ signal transduction has been suggested to be involved in many cellular processes, such as abscisic acid (ABA)-induced stomatal closure (Gilroy et al 1990;Staxe´n et al 1999;Hunt et al 2003), pollen tube growth (Franklin-Tong et al 1996), tracheary element differentiation (Zhang et al 2002), gravity perception (Perera et al 1999), and elicitor response (Kurosaki et al 1987;Legendre et al 1993;Walton et al 1993). Recent studies have revealed that there are at least two regulatory means to terminate Ins(1,4,5)P 3 signaling pathway in plants; these are Ins(1,4,5)P 3 hydrolysis by 5¢-phosphatase and Ins(1,4,5)P 3 1¢-phosphatase .…”
Section: Introductionmentioning
confidence: 99%